Molecular genetics of inherited cystic kidney diseases: new diagnostic approaches - Aquilano, Adelia <1986> (Alma Mater Studiorum - Università di Bologna, 2014)

(untitled)
Background. Hhereditary cystic kidney diseases are a heterogeneous spectrum of disorders leading to renal failure. Clinical features and family history can help to distinguish the recessive from dominant diseases but the differential diagnosis is difficult due the phenotypic overlap. The molecular diagnosis is often the only way to characterize the different forms. A conventional molecular screening is suitable for small genes but is expensive and time-consuming for large size genes. Next Generation Sequencing (NGS) technologies enables massively parallel sequencing of nucleic acid fragments. Purpose. The first purpose was to validate a diagnostic algorithm useful to drive the genetic screening. The second aim was to validate a NGS protocol of PKHD1 gene. Methods. DNAs from 50 patients were submitted to conventional screening of NPHP1, NPHP5, UMOD, REN and HNF1B genes. 5 patients with known mutations in PKHD1 were submitted to NGS to validate the new method and a not genotyped proband with his parents were analyzed for a diagnostic application. Results. The conventional molecular screening detected 8 mutations: 1) the novel p.E48K of REN in a patient with cystic nephropathy, hyperuricemia, hyperkalemia and anemia; 2) p.R489X of NPHP5 in a patient with Senior Loken Syndrome; 3) pR295C of HNF1B in a patient with renal failure and diabetes.; 4) the NPHP1 deletion in 3 patients with medullar cysts; 5) the HNF1B deletion in a patient with medullar cysts and renal hypoplasia and in a diabetic patient with liver disease. The NGS of PKHD1 detected all known mutations and two additional variants during the validation. The diagnostic NGS analysis identified the patient’s compound heterozygosity with a maternal frameshift mutation and a paternal missense mutation besides a not transmitted paternal missense mutation. Conclusions. The results confirm the validity of our diagnostic algorithm and suggest the possibility to introduce this NGS protocol to clinical practice.